2011
DOI: 10.1186/ar3364
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal networks of immune response-related molecules in bone marrow cells from patients with rheumatoid arthritis as revealed by DNA microarray analysis

Abstract: IntroductionRheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic synovitis that progresses to destruction of cartilage and bone. Bone marrow (BM) cells have been shown to contribute to this pathogenesis. In this study, we compared differentially expressed molecules in BM cells from RA and osteoarthritis (OA) patients and analyzed abnormal regulatory networks to identify the role of BM cells in RA.MethodsGene expression profiles (GEPs) in BM-derived mononuclear cells from 9 RA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…Importantly, recent studies are combining enrichment and module-based methods to point to broader findings. For example, network analysis of enriched pathways revealed major roles for antigen presentation and interferon signaling in rheumatoid arthritis [58]. …”
Section: Analytical Methods To Detect Pathway-phenotype Relationshipsmentioning
confidence: 99%
“…Importantly, recent studies are combining enrichment and module-based methods to point to broader findings. For example, network analysis of enriched pathways revealed major roles for antigen presentation and interferon signaling in rheumatoid arthritis [58]. …”
Section: Analytical Methods To Detect Pathway-phenotype Relationshipsmentioning
confidence: 99%
“…The finding that levels of IL-6 and IL-8 were markedly elevated in BM aspirates from RA patients (compared with controls) [15] is suggestive of ongoing pathology in the BM region. DNA microarray analysis also demonstrated that BM cells from RA patients have abnormal functional networks in immune response and cell cycle when compared to those from osteoarthritis patients, with overexpression of genes that take part in the antigen presentation pathway and interferon signaling [16]. Studies in experimental arthritis have confirmed a generalized pattern of red marrow conversion with enhanced myelopoiesis in conjunction with either increased IL-1 and IL-6 activity [17] or TNF overexpression [18].…”
Section: Histopathology Of the Bone Marrow In Rheumatoid Arthritismentioning
confidence: 99%
“…Более того, высокая базальная экспрессия TNFa у больных, у которых концентрация С-реактивного белка (СРБ) в крови после терапии уменьшалась до уровня, наблюдаемого у здоровых лиц, оказалась маркером эффективности терапии ингибитором TNFa, инфликсимабом [20]. Отрицательная корреляция базальной экспрессии гена TNFa с числом болезненных и припухших суставов после терапии метотрексатом (МТ) у больных ранним РА также свидетельствует о прогностическом потенциале экспрессии гена TNFa для оценки эффективности 11 пар монозиготных близнецов Многочисленные гены с повышенной или пониженной экспрессией у близнецов больных РА по сравнению со здоровыми сибсами [150] 9 больных РА и 10-ОА Повышенная экспрессия генов регулирующих иммунный ответ [157] антиревматической терапии [21]. Это подтверждается сообщением о том, что повышенная экспрессия генов провоспалительных цитокинов у пациентов, чувствительных к терапии антителами к TNFa, нормализуется быстрее, чем у неответчиков [22], что может быть связано с ослаблением некоторых иммунных путей у данных больных [23].…”
Section: экспрессия фактора некроза опухолей альфа и интерферонов 1 тunclassified
“…[источник] TNFa [14] S100 Са-связывающий белок А8 [89] MMP-9 [95] IL-1b [90] ASICs [75] MMP-12 [128] IL-7R [142] TPRV1 [76,77] RANKL [116,117] IL-2 индуцируемая киназа Т-лимфоцитов [157] NGF [80] OPG [114] Регуляторы активации Т-лимфоцитов [157] Рецептор лимфотоксина [81] Катепсины В, К, L [125] Хемокины и их рецепторы [157] Эндоканнабиноиды [82] MMP-1 [129] р53-связывающий белок [150] Антагонисты PPARa [82] MMP-3 [130] Рецептор Т-лимфоцитов [157] Опиоидные рецепторы [84] MMP-13 [132] Регуляторы активации Т-лимфоцитов [157] Антагонисты опиоидных рецепторов [84] Cелектин [150] Рецептор фракталкина CX3CR1 [86] RUNX3 [113] IL6 [31] ULK1 [96,140] …”
Section: деструкция суставовunclassified